817 DT095895, a selective EP4 receptor antagonist with monotherapy efficacy in syngeneic mouse model(s) and best-in-class properties. (9th November 2020) - Blayo, Anne-Laure; Deshons, Laurène; Dumont, Alexia; Franchet, Christel; Halter, Célia; Herbin, Ludovic; Hommet, Gaël; Mayer, Stanislas; Bessede, Alban; Nafia, Imane; Sidhoum, Marjorie; Leroy, Xavier; et al.
Abstract : Background: Elevated levels of Prostaglandin E2 (PGE2), an eicosanoid notably synthesized by the cyclooxygenase-2 (COX-2), exert strong immunosuppressive effects in the tumor microenvironment. COX-2-positive solid tumors have the ability to use this pathway as a resistance mechanism, especially to escape from the host immune system, thus limiting the anti-tumor effects of immune checkpoint inhibitors (ICI). These immunosuppressive effects are largely mediated by the EP4 receptor, expressed on multiple immune cells. Methods: A novel series of EP4 receptor antagonists has been developed, with improved pharmacokinetic properties when compared to the EP4 receptor antagonists currently being evaluated in clinical trials. An intensive lead optimization program led to the identification of DT095895, a small molecule development candidate with a 'best-in class' potential. DT095895 was assessed in multiple syngeneic mouse tumor models selected for their COX-2 expression profile. Results: DT095895 preclinical package will be presented in the poster. Efficacy was seen both in a monotherapy setting, as well as in combination with an ICI. Additionally, a specific biomarker program was implemented and validated in order to show target engagement. A phospho-flow murine whole blood assay was set-up to assess the ability of DT095895 to inhibit CREB phosphorylation induced by a selective EP4 receptor agonist in CD3+ cells. This biomarker was further developed for human whole blood to support Phase 1 and clinical trials studies. Conclusions: DT095895 is a selective EP4 receptor antagonist and demonstrates strong anti-tumor effects in multiple syngeneic mouse tumor models, both as a monotherapy and in combination with ICI, through the inhibition of the PGE2-induced immunosuppression. DT095895 progresses in regulatory development.